Complaint resolution management expectations in an asymmetric business-to-business context - Thorsten Gruber; Stephan C. Henneberg; Bahar Ashnai; Peter Naude; Alexander E. Reppel (2010)
Purpose – The purpose of this paper is to gain a deeper understanding of the attributes of effective complaint management in business-to-business relationships, and to reveal the underlying benefits that buying organizations are looking for when complaining. Design/methodology/approach – A semi-standardized qualitative technique called laddering was applied successfully to an online environment with 22 representatives of companies in the manufacturing industry participating. Findings – The resulting hierarchical value map displays 13 attributes which exemplify the complaint resolution management expectations. A total of 14 constructs represent consequences of such resolution activities, while four constructs can be interpreted as values. Take “Quick action” is the most important of the expected attributes and behaviours of complaint resolution management. Four consequences seem to dominate the assessment: Financial benefits, Prevention of future problems, Solution, and Effective resolution handling. “Maintain supplier relationships” appears as a dominant value in the perceptions of respondents, with half of them mentioning this as an end. Research limitations/implications – Owing to the exploratory nature of the study in general and the scope and size of its sample in particular, the findings are tentative in nature. The study involved a group of representatives of large UK manufacturing companies with complaint handling responsibilities and so the results cannot be generalised. Originality/value – The findings enrich the existing limited stock of knowledge on complaint management in business relationships by developing a deeper understanding of the attributes that complaining customer companies desire from suppliers, as well as the underlying business logic (i.e. values) for these expectations. The quality of the results also suggests that the laddering questionnaire technique can be transferred effectively to an online environment.